Surgical treatment of acute hemorrhagic gastritis - Leborgne, Raúl (Cirugía del Uruguay, 1974)
The principal function of a radiologist is to make a diagnosis of a palpable nodule. It is essential to be able to clearly visualize the nodule, so as to be able to determine the characteristics of its interna! structure, including calcification, shape, borders outline and details of infiltration. For this purpose, the author has constructed a frame which is adaptable to the cone of an X-Ray apparatus, and makes it possible to compress the maroma on the X-Ray Table, thus obtaining excellent photographs of the nodules if examined in this manner.